NCAM1-SHIP2 axis upon recognizing microbes inhibits the expressions of inflammatory factors through P38-H3K4me and P38-NF-κB pathways in oyster - Jiejie Sun; Xiangqi Shi; Mengjia Wang; Muchun He; Wenwen Yang; Linsheng Song (Cell Communication and Signaling)
Abstract Neural cell adhesion molecule 1 (NCAM1/CD56) as a well-known surface marker for natural killer (NK) cells plays important roles in cell migration, adhesion, and inflammation. In the present study, NCAM1 homolog containingthree immunoglobulin domains, one fibronectin type 3 domain, a transmembrane region and a cytoplasmic tail with two intracellular immunoreceptor tyrosine-based inhibitory motifs (ITIMs) was identified from the Pacific oyster, Crassostrea gigas (defined as CgNCAM1). The mRNA transcripts of CgNCAM1 were highly expressed in haemocytes. The mRNA expressions of CgNCAM1 in haemocytes increased significantly after Vibrio splendidus stimulation. The positive green signals of CgNCAM1 and SH2-containing inositol 5-phosphatase (CgSHIP2) could translocate onto the haemocyte membrane after V. splendidus stimulation. The recombinant extracellular domains of CgNCAM1 exhibited binding activity towards various pathogen-associated molecular patterns (PAMPs) and microbes. Upon binding to its ligands, CgNCAM1 recruited CgSHIP2 to transduce inhibitor signals to reduce the phosphorylation of CgP38. The inhibition of CgP38 reduced the methylation of histone H3K4 and nuclear translocation of NF-κB, which eventually inhibited the mRNA expressions of inflammatory factors (CgIL17-2/3/6 and CgTNF-2) to suppress inflammation. These results suggested that CgNCAM1 could function as an immune checkpoint to sense different PAMPs and microbes and reduce the inflammation through inhibiting P38-epigenetic and P38-NF-κB pathways in oysters.